Decoding the mitogenome of rosemary (Salvia rosmarinus): insights into genome evolution, structural dynamics and prospects for mitochondrial engineering - Yuqing Feng; Yonghui Liu; Jizhe Han; Yanbo Huang; Joongku Lee; Goro Kokubugata; Zhechen Qi; Xiaoling Yan (BMC Plant Biology)
Abstract Background Rosemary (Salvia rosmarinus), an aromatic evergreen shrub of the Salvia (Lamiaceae), is native to the Mediterranean region, thriving in rocky or arid soils. Widely used in food, pharmaceuticals, and cosmetics, its clonal reproduction poses significant challenges for breeding and germplasm innovation. While mitogenome engineering holds promise for introducing heritable mutations, incomplete mitogenome information for rosemary has hindered such efforts. This study addresses this gap by assembling and analyzing the complete mitogenome of S. rosmarinus, focusing on its structure, repetitive sequences, RNA editing events, intracellular gene transfer (IGT), and phylogenetic relationships. Results The S. rosmarinus mitogenome spans 384,113 bp with a GC content of 44.8%, containing 34 unique protein-coding genes and 114 simple sequence repeats. Comparative analysis revealed 28 homologous segments shared between the mitogenome and plastome, totaling 18,675 bp in length. Furthermore, homologous fragments between nuclear and organellar genomes were identified, including 1,069,255 bp of organelle-derived sequences in the nuclear genome, with 194,689 bp from nuclear plastid DNA transfers (NUPTs) and 15,192 bp from nuclear mitochondrial DNA transfers (NUMTs). NUPTs were more abundant and contributed more significantly to the total length. Synteny analysis of eight Lamiales species revealed extensive mitogenomic recombination and structural rearrangements. These findings highlight the dynamic nature of mitogenomes, offering insights into genome evolution and supporting future breeding programs to enhance the genetic diversity and adaptability of S. rosmarinus. Conclusions This study provides the first complete mitogenome of S. rosmarinus, revealing dispersed repeats, RNA editing, and horizontal gene transfer between the nuclear and organelle genomes. The mitogenome exhibits a typical circular structure with evidence of frequent recombination, providing valuable insights into Salvia mitochondrial genetics, genome evolution, and molecular biology.